2015
DOI: 10.1111/eff.12268
|View full text |Cite
|
Sign up to set email alerts
|

Autumn food restriction reduces smoltification rate, but not over‐winter survival, in juvenile brown trout Salmo trutta

Abstract: The winter is often considered as a survival bottleneck for stream-living fish. Juvenile salmonids generally become less active during this period, and while food intake continues to some extent, growth rates are typically low. Here we present the results of an over-winter field experiment where energy levels were manipulated in late autumn. Three groups of juvenile (age 1+) brown trout, from an anadromous population, were monitored with respect to over-winter growth rate and survival (as indicated by recaptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…() did not see any effect of over winter feed restriction on smolting rate in S. salar either. In contrast, in the closely related S. trutta , feed restrictions in the autumn decrease the smolting rate in the spring (Näslund et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…() did not see any effect of over winter feed restriction on smolting rate in S. salar either. In contrast, in the closely related S. trutta , feed restrictions in the autumn decrease the smolting rate in the spring (Näslund et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Jones, Bergman, and Greenberg (2015) demonstrated that reduced winter and spring feeding increased the tendency to smoltify for lake feeding brown trout from the River Klarälven, Sweden. In contrast, another experiment reported that trout facing food restriction in late autumn exhibited lower rate of silvering, which is indicative of a delay in smolting (Näslund, Sundström, & Johnsson, 2015). Thus, winter/beginning of spring appears to be a critical period when the decision is made about whether to smolt and migrate to a better feeding area.…”
Section: The Energy Surplus Hypothesismentioning
confidence: 93%
“…However, the effect of resource availability on migration is not clear. For example, a reduction in food availability can result in lower body condition and fat content and increased smoltification (Jones, Bergman, & Greenberg, ) but has also been shown to reduce migration (Midwood, Larsen, Aarestrup, & Cooke, ) or delay smoltification (Näslund, Sundström, & Johnsson, ). Females are more likely to migrate, mature later, and at a larger body size (Klemetsen et al, ) than males, and the difference in fecundity between large and small female fish can result in differences in trout population dynamics (via egg and juvenile density; Elliot, ), even at small geographic scales.…”
Section: Introductionmentioning
confidence: 99%